Geology Roof Control And Mine Design - Syd S. Peng; Gerald L. Finfinger (The National Institute for Occupational Safety and Health (NIOSH))
Geology is an integral part of roof control, mine design, and production operations. Yet, the importance of geology, coal/rock as an engineering construction material and its properties and behavior within the planned mine areas, in overall mine production operations has not been hilly appreciated. Of all of the engineering disciplines, mining engineers work with the most challenging construction materials. They must deal with rock materials as they exist in their natural states and design mine structures without well-known and defined properties. Further complicating the design process is the variability of the in-situ rock materials with rock types and rock properties varying widely from place-to-place. Predicting properties in advance of mining is difficult and oftentimes impossible. This is why some types of roof-control failures may suddenly occur in some areas when a single roof-control technique is consistently applied to an entire panel, section, or mine. Many roof-control techniques are primarily applicable to the geological conditions that were assumed in the development of those techniques and variations of the rocker rock properties may require modification or significant redesign of the support technology.